Social protection: Towards gender equality - Michael MacLennan; Raquel Tebaldi; Flora Myamba; John Stacey (International Policy Centre for Inclusive Growth (IPC-IG), 2017)
Social protection has become prominent in the global development agenda over recent decades, with social protection systems now being included as a target under Sustainable Development Goal 1: "End poverty in all its forms everywhere". In developing countries, these policies have played an important role in alleviating extreme poverty, among other impacts that are increasingly being investigated. Beyond the improvement of the material conditions of beneficiaries, measures that take into account the power dynamics and inequalities within households and communities are needed for social protection programmes to properly address gender inequality in a transformative way. This special edition of Policy in Focus, which is auspiciously being released for International Women's Day 2017, covers key topics related to gender equality and social protection, featuring a wide range of contributions from women policy practitioners and scholars, presenting case studies and reflections from Brazil and various African countries.
Keywords: 330; Social protection; gender; equality